Risk and Aging Vascular in a city population - Ruiz Mori, Enrique (2016)
Objetive: Cardiovascular diseases that every year have more prevalence in the country, are the product of risky factors, many of them modifiable and preventable. The objective of the present study has been to know and analyze the factors of cardiovascular risk and determine the vascular age in the population of Lima. Material and methods: A descriptive cross sectional study, carried out in March 2016, in the southern, northern and eastern cones of Metropolitan Lima, in people older than 30 and younger than 75 years old. The survey structured for the study collected the following variables: gender, age, arterial hypertension, smoking, diabetes, physical activity and type of diet. Blood presure, weight and tall were recorded. Results: In total, 485 participants were included, 197 men and 288 women. The age was 49,5± 9,9 years old. The more frequent risky factor was the unhealthy diet (47,6%), followed by sedentary lifestyle (42,5%). Arterial hypertension was observed in 20,8%, being more frequent in men. 85.2% did not smoke and overweight was found in 47.2%, being its frequency higher in women. The low risk was determined in 60,4% and it was predominant in women, while higher risk was 18.6% in men. The average cardiovascular age was higher in 1,4 years compared to the chronological age beign more marked in men, in whom the difference was 5,8 years between 50 and 59 years old. Conclusions: The more frecuente cardiovascular risk has been unhealthy diet followed by sedentary lifestyle. The high risk was 18,6% predominating in men. Men between 50 and 59 years old have a cardiovascular age 5,8 years higher than the chronological age.